Effect of Gd and Ti co-doping on electrical performance of Bi2O3 oxygen ion conductor. (1st January 2022) - Yang, Qiang; Luo, Zeyang; Zhu, Pei; Wei, Yunhe; Wang, Huan; Yan, Duanting; Wang, Dejun; Liu, Runru
Abstract: In this study, a new oxygen ion conductor electrolyte material with high conductivity was reported. Bi2 O3 was co-doped with Gd2 O3 and TiO2 by solid-phase synthesis method to obtain Bi1–3x Gd2x Tix O1.5+ δ and Bi0.76 Gd0.18−x Tix O1.5+ δ (TGSB) ceramics. The phase composition, surface morphology and electrical properties of TGSB samples were characterized by x-ray diffraction (XRD), scanning electron microscope (SEM) and AC impedance respectively. XRD results show that only 6T12GSB has a single cubic fluorite structure, and impurity phases appear in other samples. The SEM results show that only when the doping concentrations of Gd and Ti are 12 mol% and 6 mol% respectively, the particle size is relatively smaller and there are no obvious pores. From the analysis of electrical properties, Gd dopant is helpful to the stability of the Bi2 O3 phase than Ti dopant, but not beneficial to higher conductivity. When the doping concentration of Gd is higher than 16 mol%, it becomes more stable. The conductivity of the 6T12GSB sample is relatively high. The conductivity of the TGSB samples is higher than that of the TLSB samples under the lower temperature condition (<450 °C), and the electrical performance of Bi2 O3 -based materials are enhanced especially at low temperature.